1987
DOI: 10.1002/zaac.19875450227
|View full text |Cite
|
Sign up to set email alerts
|

Massenspektroskopische Untersuchung der Borfluorid‐Komplexe ABF4

Abstract: Die Komplexe ABF4, die sich beim Erhitzen nach ABF4,f,fl  AF,f + BF3 (A  LiCs) zersetzen, geben neben BF3 auch A2(BF4)2‐Moleküle (A  K, Rb, Cs) an die Gasphase ab. Auftrittspotentiale wurden bestimmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…14,15,35 The Tdec_calc of LiBF4 in Table 4 is certainly higher than that of LiPF6, which agrees with the experimental data. [18][19][20][21][22]35 Since the difference between ΔdecH°298 values of the two compounds is not large compared with the difference between ΔdecS°298 values, the contribution of the latter is expected to be dominant. When one compares thermal stabilities of MBF4 and MPF6, where M is common, MBF4 seems to have an advantage of being thermally more stable than MPF6 from the equations ( 4) and ( 5) because S°(BF3) is smaller than S°(PF5) and S°(MF)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,35 The Tdec_calc of LiBF4 in Table 4 is certainly higher than that of LiPF6, which agrees with the experimental data. [18][19][20][21][22]35 Since the difference between ΔdecH°298 values of the two compounds is not large compared with the difference between ΔdecS°298 values, the contribution of the latter is expected to be dominant. When one compares thermal stabilities of MBF4 and MPF6, where M is common, MBF4 seems to have an advantage of being thermally more stable than MPF6 from the equations ( 4) and ( 5) because S°(BF3) is smaller than S°(PF5) and S°(MF)…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, LiBF4 is thermally more stable than LiPF6. [18][19][20][21][22] The effect of structural characteristics of LiBF4 on its thermal decomposition temperature will be described using thermodynamic calculations to explain the higher thermal stability of LiBF4 than LiPF6.…”
Section: Introductionmentioning
confidence: 99%
“…If the XeI* formation is initiated by the ''harpoon'' mechanism, the cross section can be approximated as pr c 2 by using r c of eqn (9), 28 e 2 /r c E IE (Xe* ( 3 P 2 )) À EA (CH 3 I) (9) where IE (Xe* ( which the 6s electron jump takes place because Coulomb forces between the ions [Xe + ( 2 P 3/2 ) À I À ( 1 S 0 )] essentially ensure XeI* formation. According to IE (Xe* ( 3 P 2 )) = 3.82 eV 29 and EA (CH 3 I) = 0.11 eV, 30 r c is calculated to be 3.9 A ˚. Because the 6s electron jump should take place at a relatively small distance, we can expect the large difference in the reaction probability at the two ends (I-end and CH 3 -end).…”
Section: Comparison With the Harpoon Mechanismmentioning
confidence: 98%
“…Indeed, for the KI formation in the K + CF 3 I reaction system which has an large crossing distance of r c = 5.2 A ˚(IE (K) = 4.35 eV 40 and EA (CF 3 I) = 1.57 eV 38 ), it has been reported that the molecular orientation exerts an influence on only the angular distribution of KI with comparable reaction probability at the two ends. 4 Moreover, for the KCl formation in the K + CHCl 3 reaction system which has a shorter crossing distance of r c = 3.9 A ˚2 (IE (K) = 4.35 eV 40 and EA (CHCl 3 ) = 0.62 eV 41 ), it has been reported that the molecular orientation has no influence on the reaction probability and on the angular distribution of KCl. 3 Therefore, the observed large steric effects for the XeF* formations are distinctly different from the expectation from the large crossing distance r ad c estimated from the adiabatic electron affinity of NF 3 .…”
Section: Comparison With the Harpoon Mechanismmentioning
confidence: 99%
“…It seems likely that this depletion is caused by the dark channel via a similar indirect process that have been commonly proposed in the other reaction systems; i.e., the NF 3 * formation via the backelectron transfer from the dissociating (NF 2 Á Á ÁF À ) to Xe + which may be favorable for the sideways collision. The electron transfer from the NF 2 segment to Xe + might be energetically possible because the ionization energy of Xe (IE (Xe) = 12.13 eV 41 ) is slightly larger than that of NF 2 (IE (NF 2 ) = 11.8 AE 0.4 eV 46 ). In addition, since the direct coupling between the entrance surface [Xe*( 3 P 2 ) + NF 3 ] and the exit surface [Xe + NF 3 *] via a mechanism like electron exchange is expected at the short intermolecular distance, the NF 3 * formation via direct coupling might have some effect on the stereo-anisotropy of the XeF* formation, too.…”
Section: G Effect Of Dark Channelmentioning
confidence: 99%